Transformations of the Food Practices in Modern Russia: the Institutional and Discursive Determinants - N. N. Zarubina (Vestnik MGIMO-Universiteta)
The author analyzes the transformation of the Russian food practices and reveals their discursive and institutional determinants. Feeding practices go beyond the satisfaction of biological needs of human food. They include a range of habitual actions, structured by the rules that are not determined by the physiology and the economy as a system of food production, but social institutions, cultural values, traditions and dominant discourses. Dynamics of food plays practices inherent peculiarities of Russian modernization transformations, which consist in the inversion transition character diametrically opposite types of the institutional organization and value orientations. During the period of economic reforms of the 90-th years of the twentieth century, there was a sharp institutional transition from the Soviet system of distribution of the food to the market system. It turned out to shock for most of the population and led to a controversial change in food practices. On the one hand, the deficit of food disappeared, on the other hand due to the socio-economic stratification the inequality has increased. In addition, the food market was almost completely dominated by profit-oriented manufacturers and retailers, which gave rise to problems of quality and food safety. These problems led to the actualization and interpenetration of medikalized and environmental discourses which reflect a massive concern. The food market development has also led to the marketization and spektaklization of the food practices. This is reflected in the promotion of products through a system of symbols that appeal to irrational emotions, myths, habits and traditions. Diverse discourses of the food practices - medikalizationed, environmental, hedonistic and other discourses, appear as a show representing the various, sometimes conflicting, rules of everyday activities. The functionality of the spektaklization is that it maintains an interest in the field of nutrition as a cultural phenomenon; emphasizes its importance and value. The spektaklization of food is in line traceable to the post-Soviet period general trend of increasing attention to the daily life, transforming it from a repressed and insignificant in the scope of the object of attention and cultivation.